Assessing the environmental performance of vermicompost from spent coffee grounds based on a life cycle approach - Bhanupong Phrommarat; Pongsri Paopuree (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose: This study investigated the physicochemical properties of vermicompost from spent coffee grounds (SCG) and assessed its environmental performance using Life Cycle Assessment (LCA). Additionally, the environmental performance of vermicompost was compared to other waste treatment and utilization scenarios.